Size-independent, between-individual variability in feed ingestion rate in European seabass (Dicentrarchus labrax) - Joaquim Tomàs-Ferrer; Irene Moro-Martínez; Enrique Massutí-Pascual; Amàlia Grau; Miquel Palmer (PLoS ONE, 2026)
Understanding between-individual variability in energy acquisition is essential for elucidating many ecological processes in wild fish populations and for enhancing the efficiency of aquaculture production. This study explores whether individual variations in feed ingestion rates among group-reared fish can arise from intrinsic fish-specific, size-independent factors. Specifically, we quantify the residual variability in ingestion rate (i.e., the variability beyond body size effects and extrinsic influences) to assess the role of context-independent, stable, intrinsic behavioural differences that may lead to feeding hierarchies. We monitored the individual feeding behaviour of 48 European seabass adult females ( Dicentrarchus labrax) externally tagged reared in sea cages (6 cages housing 8 fish each) under three feeding levels (two cages per level) over four months. Across 8 repeated feeding trials per cage, fish were offered feed pellets one at a time using an automated feeder, and their individual pellet consumption were video recorded. Using a Bayesian statistical model, we evaluated the fish-specific probability of pellet consumption as a function of body size, temperature, anthropogenic stress and feeding level, while accounting for variation across individuals and feeding trials. Our results showed: i) a substantial and consistent between-individual variability in ingestion rates across feeding trials, and ii) a relevant negative effect of anthropogenic stress on feeding activity. Notably, individual-specific effects, independent of body size and external variables, accounted for over 70% of the variance in ingestion rate, suggesting that intrinsic and stable behavioural differences, indicative of fish behavioural types, may play a central role in shaping feeding hierarchies.